RITUAL TAHLILAN SEBAGAI MEDIA DAKWAH - Kholilurrohman Kholilurrohman (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2010)
Tahlilan term comes from the word hallala yuhallilu tahlillan, namely reading the sentence La ilaha illallah.Tahlilan can be used as one of the elements of dakwah that is as dakwah media. Tahlilan, when viewed from the function,has several benefits for society as silaturrahmi media, social control, and also can function psychologically for reassurance